Good care practices can mitigate the negative effects of poverty and low maternal schooling on children's nutritional status: evidence from Accra - Ruel, Marie T.; Levin, Carol E.; Armar-Klemesu, Margaret; Maxwell, Daniel G.; Morris, Saul Sutkover (International Food Policy Research Institute, 1999)
This study uses data from a representative survey of households with preschoolers in Accra, Ghana to (1) examine the importance of care practices for children’s height-for-age z-scores (HAZ); and (2) identify subgroups of children for whom good maternal care practices may be particularly important. Good caregiving practices related to child feeding and use of preventive health services were a strong determinant of children’s HAZ, specially among children from the two lower income terciles and children of children’s HAZ, specially among children from the two lower income terciles and children whose mothers had less than secondary schooling. In this population, good care practices could compensate for the negative effects of poverty and low maternal schooling on children’s HAZ. Thus, effective targeting of specific education messages to improve child feeding practices and use of preventive health care could have a major impact on reducing childhood malnutrition in Accra.